Round window plugging in the treatment of superior semicircular canal dehiscence. (9th October 2017) - Succar, Eric F.; Manickam, Periakaruppan V.; Wing, Sara; Walter, Jeffrey; Greene, Joseph S.; Azeredo, William J.
Abstract : Objectives/Hypothesis: Objectives were to describe the use of round window plugging for superior semicircular canal dehiscence syndrome and review further recommendations regarding the procedure based on our experience and to compare results with recent literature on round window plugging. Study Design: Retrospective case series. Methods: Fourteen patients underwent round window plugging for superior semicircular canal dehiscence at our institution from 2012 to 2015. All patients underwent the same surgical procedure. Available pre‐ and postoperative data were reviewed. Results: Fourteen patient charts were reviewed. Symptoms of autophony improved in nine of 14 (64%) patients. Symptoms of pressure‐induced vertigo improved in seven of 12 (58%) patients. Hennebert's sign that was positive preoperatively only improved in one of six (17%) patients. A positive preoperative vestibular evoked myogenic potential improved in only one of six (17%) patients. Six of 13 (46%) patients had increased air conduction thresholds postoperatively. Conclusions: Round window plugging has been described as a less‐invasive treatment for patients with superior semicircular canal dehiscence. Although the procedure did benefit some of our patients, successful outcomes were not predictable. Improvement in at least one objective finding was seen in only 21% of the patients studied. Hennebert's sign and vestibular evoked myogenic potentials that were positive preoperatively only improved in 17% of patients. At our institution, round window plugging is no longer considered a reasonable treatment option for most patients with superior semicircular canal dehiscence. We recommend that further study on this topic follow a standardized pre‐ and postoperative assessment. Level of Evidence: 4. Laryngoscope, 128:1445–1452, 2018